Towards a Walking-Based Pedagogy - Pyne Feinberg, Pohanna (Journal of the Canadian Association for Curriculum Studies, 2016)
After several years of experimenting with walking as a creative process and an artistic form, my commitment to developing walking-based pedagogy for art education has been honed and heartened. This article details my doctoral research and summarizes the mindful walking methodology I am developing for diverse demographics and variable geographies. In particular, I share excerpts from interviews conducted with four Montreal-based artists who walk as an aspect of their practice: Victoria Stanton, Kathleen Vaughan, karen elaine spencer, and Dominique Ferraton. Presented as a hybrid article that couples a written introduction with a self-directed audio walk, the two components are designed to complement one another. By providing an audio walk as a pedagogical tool, I am advocating for kineasthetic engagement as an essential component for discourse on this topic. Likewise, I propose a notion of curriculum that is lived and emerging, somatic and contextual, personal yet political, and enhanced by curiosity and listening.